A Spatial Analysis of Body Mass Index and Neighborhood Factors in Community-Dwelling Older Men and Women. (June 2016) - Christman, Zachary; Pruchno, Rachel; Cromley, Ellen; Wilson-Genderson, Maureen; Mir, Izza
The spatial distribution of obesity among the older population can yield insights into the influence of contextual factors associated with this public health problem. We tested the relationship between neighborhood-level characteristics and body mass index (BMI) using global and local spatial statistics of geographic clustering, using data derived from a random-digit-dial sample of 5, 319 community-dwelling adults aged 50 to 74 residing in 1, 313 census tracts in New Jersey. Geographically weighted regression modeled associations between BMI clusters and neighborhood characteristics, including metrics of structure, safety, demographics, and amenities. Across the sample panel, average BMI was 28.62 kg/m 2 for women and 28.25 kg/m 2 for men. There was significant spatial clustering of obesity by census tract, varying by gender across the state. Neighborhood characteristics were more strongly related to BMI for women than men. This research illuminates the role of neighborhood contextual factors and will assist community planners, officials, and public health practitioners as they address the rise in obesity.